Image-Guided Radiotherapy for Cardiac Sparing in Patients with Left-Sided Breast Cancer - Lemanski, Claire; Thariat, Juliette; Ampil, Federico L.; Bose, Satya; Vock, Jacqueline; Davis, Rick; Chi, Alexander; Dutta, Suresh; Woods, William; Desai, Anand; Godinez, Juan; Karlsson, Ulf; et al. (Frontiers in Oncology, 2014)
Patients with left-sided breast cancer are at risk of cardiac toxicity because of cardiac irradiation during radiotherapy with the conventional 3-dimensional conformal technique (3D-CRT). In addition, many patients may receive chemotherapy prior to radiation which may damage the myocardium and may increase the potential for late cardiac complications. New radiotherapy techniques such as intensity-modulated radiotherapy (IMRT) may decrease the risk of cardiac toxicity because of the steep dose gradient limiting the volume of the heart irradiated to a high dose. Image-guided radiotherapy (IGRT) is a new technique of IMRT delivery with daily imaging which may further reduce excessive cardiac irradiation. Preliminary results of IGRT for cardiac sparing in patients with left-sided breast cancer are promising and need to be investigated in future prospective clinical studies.